Potent neutralizing monoclonal antibodies against Ebola virus isolated from vaccinated donors - Pengfei Fan; Xiangyang Chi; Guodong Liu; Guanying Zhang; Zhengshan Chen; Yujiao Liu; Ting Fang; Jianmin Li; Logan Banadyga; Shihua He; Changming Yu; Xiangguo Qiu; et al. (Taylor & Francis Group, 2020)
Ebola virus (EBOV) can cause severe hemorrhagic fever in humans, and no approved treatment is currently available. Although several antibodies have achieved good protection in animal models, the potential emerging isolates of ebolavirus and the unknown effects of experimental antibodies in humans underscore the need to develop additional antibodies to address the threat of Ebola. Here, we isolated a series of memory B cell-derived monoclonal antibodies from healthy Chinese adults vaccinated with Ad5-EBOV. These antibodies were encoded by diverse germline genes and had high levels of somatic hypermutation. Most antibodies were cross-reactive and could bind at least two ebolavirus glycoproteins (GPs). Seven neutralizing antibodies were identified using HIV-EBOV GP-Luc pseudovirus, and they effectively neutralized authentic EBOV. In particular, monoclonal antibody 2G1 exhibited potent cross-neutralization against HIV-EBOV/SUDV/BDBV GP-Luc bearing different ebolavirus GPs. We used truncated GPs, competition assays, and software prediction to analyze seven neutralizing antibodies, which bound four different epitopes on GP. Importantly, three of these antibodies provided complete protection in mice when administered one day post-infection. Our study expands the list of candidate antibodies and the options for successfully treating ebolavirus infection.